Desafíos que enfrenta la cooperación internacional en Colombia: una mirada al contexto de los proyectos de desarrollo social, 2016 - 2021, en el Valle del Cauca. (2022)
International cooperation is thought of as a joint exercise for the articulation of the economic and social development of countries, through the transfer of technologies, knowledge, experiences or resources by countries with the same or higher level of development. Colombia is going through great challenges to overcome; therefore, the assistance of international cooperation has been turning to support to correct inequities.